Role of Livestock Husbandry on Rural Transformation in North India: A case study - Iqubal, Asif (Journal for Geography, 2010)
Livestock husbandry is an important source of economic activity in the agricultural sector contributing a major portion of GDP to India and improving the socio-economic conditions for people in general and rural people in particular. Livestock husbandry has been practiced, usually in rural areas, since ancient times. The increasing urbanization of the growing popula-tion and the changing food habits of people has enhanced the demand of livestock products worldwide. Thus, the world’s livestock sector is growing at an unprecedented rate in developing countries. India is one developing country that shares the largest number of livestock and has a top position in milk production in the world. The livestock in India with 185 million cattle and 98 million buffaloes possesses 20% of the world’s bovine and 14% of the world’s cattle population. A micro level geographical area known as Aligarh district in north India has been selected for study. The data regarding various aspects of livestock husbandry at the grass roots level is not available in recorded form. 12 villages from the district have been selected for field survey to generate data regarding the socio economic transformation of rural people in the study region. The study revealed that livestock husbandry shows upward dynamism in terms of numbers. A positive growth of 7.5% livestock as a whole has been observed through the data analysis of two points of time i.e. 1993 and 2003. 83% of the workforce of households surveyed in the rural areas is found to be involved directly or indirectly in livestock husbandry, and it is practiced by landless, marginal and small farmers particularly.